Subfossil trees suggest enhanced Mediterranean hydroclimate variability at the onset of the Younger Dryas - Pauly, Maren; Kromer, Bernd (Scientific reports, 2018)
Nearly 13,000 years ago, the warming trend into the Holocene was sharply interrupted by a reversal to near glacial conditions. Climatic causes and ecological consequences of the Younger Dryas (YD) have been extensively studied, however proxy archives from the Mediterranean basin capturing this period are scarce and do not provide annual resolution. Here, we report a hydroclimatic reconstruction from stable isotopes (δ18O, δ13C) in subfossil pines from southern France. Growing before and during the transition period into the YD (12 900-12 600 cal BP), the trees provide an annually resolved, continuous sequence of atmospheric change. Isotopic signature of tree sourcewater (δ18Osw) and estimates of relative air humidity were reconstructed as a proxy for variations in air mass origin and precipitation regime. We find a distinct increase in inter-annual variability of sourcewater isotopes (δ18Osw), with three major downturn phases of increasing magnitude beginning at 12 740 cal BP. The observed variation most likely results from an amplified intensity of North Atlantic (low δ18Osw) versus Mediterranean (high δ18Osw) precipitation. This marked pattern of climate variability is not seen in records from higher latitudes and is likely a consequence of atmospheric circulation oscillations at the margin of the southward moving polar front.
Gesehen am 02.04.2020